Flood-Reduction Scenario Based on Land Use in Kedurus River Basin Using SWAT Hydrology Model - Santika Purwitaningsih; Adjie Pamungkas; Prima Tama Setyasa; Rahel Putri Pamungkas; Ahmad Rizky Alfian; Shafira Aulia Rosyida Irawan (Department of Urban and Regional Planning, Diponegoro University, 2020)
The rapid growth population phenomenon has causes excessive land demand for residential and economic activity. Moreover, the rapid urbanization also increases the contribution of land constrains. Land conversion from conservation to cultivation uses affects the surface runoff volume that leads to flooding. According to these problems, it is necessary to take steps to control flood in Kedurus Watershed. One of the proper urban development concept is the Water Sensitive City (WSC). The protection against flood in WSC can be accomplished with the land use arrangement that can reduces the surface runoff. The aim of this research is to determine the proper land use scenario to reduce floods in Kedurus Watershed. In order to reach this aim, the writer uses sensitivity analysis to identify the proper land use scenario to be applied in the watershed and SWAT to select the best scenario. The efforts to reduce flood through the land use scenario (scenario 2) could reduce the flood volume by 44,320.32 m3 or 8.11% of the total volume of flood in the area. The average reduction of flood volume in each sub basins is 12,92% and the highest number of reduction is 65,67% (sub basin 22).